Etyczny aspekt stylu wypowiedzi w "Tygodniku Powszechnym" (na przykładzie dyskursu migracyjnego) = Ethical aspect of the style expression in "The General Weekly" ["Tygodnik Powszechny"] (on the example of the migration discourse) - Kaczor, Monika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The sense of responsibility for what is said and written requires a reflective relation to the formulated thoughts. The attitude of subjective treatment of a man in the press releases decisively affects the effectiveness of speech. System agents (linguistic) and pragmatic (contextual) play an important role in shaping of the text world. An ethical aspect of the style expression is conditioned by the respect for moral principles in interpersonal communication. An expression of this attitude is avoiding the unethical treatment of a reductive form.
Keywords: etyka; moralność; stosowność środków językowych; tekstowa wizja świata; ethics; morality; appropriateness of language means; text vision of the world